COMPOSITION COMPRISING BAICALIN AND A PARTICULAR ACRYLIC POLYMER - WILLIEN, Maud; DOUEZAN, Stéphane; ROUDOT, Angélina (2020)
The present application relates to a composition for topical application comprising baicalin and/or at least one derivative thereof or an extract containing same, and at least one acrylic polymer, and to the use of said composition in the cosmetics and dermatology fields and in particular for caring for, for the hygiene of, for protecting and/or for making up bodily or facial skin, or for hair care, preferably for caring for bodily or facial skin. A subject of the invention is also a process for the cosmetic treatment of keratin materials, which consists in applying to the keratin materials a composition as defined above, and also the use of said composition in the cosmetics or dermatology field, and in particular for caring for, protecting and/or making up bodily or facial skin, or for hair care, preferably for caring for bodily or facial skin.